2017
DOI: 10.1134/s1075700717010026
|View full text |Cite
|
Sign up to set email alerts
|

Components of total factor productivity of the Russian economy with respect to other countries of the world: The role of technical efficiency

Abstract: ⎯The article valuates structural changes in the total factor productivity for the GDP of a number of world economies based on two samples in 1990-2010. These estimates are used to study structural changes in the total factor productivity in Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The result shows that the transformation of the mode of marine economic development and the improvement of the marine environment are mutually reinforcing [3]. Some scholars also calculated the damping effect of the marine resources and environment on the marine economy in the Bohai Rim by Romer model, and put forward the countermeasures to improve the damping effect of the marine resources and environment on the marine economic development [4,5]. Relevant scholars decomposed the total factor productivity of the marine economy and found that there is a strong spatial spill-over effect between TFP index and technological progress index, and the degree of regional openness has a positive impact on TFP index and technological progress index [6,7].…”
Section: State Of the Artmentioning
confidence: 99%
“…The result shows that the transformation of the mode of marine economic development and the improvement of the marine environment are mutually reinforcing [3]. Some scholars also calculated the damping effect of the marine resources and environment on the marine economy in the Bohai Rim by Romer model, and put forward the countermeasures to improve the damping effect of the marine resources and environment on the marine economic development [4,5]. Relevant scholars decomposed the total factor productivity of the marine economy and found that there is a strong spatial spill-over effect between TFP index and technological progress index, and the degree of regional openness has a positive impact on TFP index and technological progress index [6,7].…”
Section: State Of the Artmentioning
confidence: 99%